Biosynthesis of polypeptides of cytochrome c oxidase by isolated mitochondria. - Poyton, R O (1975)
Yeast mitochondria, incubated with radioactive amino acids in a "protein-synthesizing mixture" containing an oxidizable substrate and an ATP regenerating system, have been shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis to incorporate label into polypeptides equivalent in molecular weight and relative amount ot those made in vivo in the presence of cycloheximide. The ability of these isolated mitochondria to synthesize "native" polypeptides was assessed by examining the incorporation of label into subunits of cytochrome c oxidase (EC 1.9.3.1). An analysis of immunoprecipitates formed by incubating cholate extracts of labeled mitochondria with an antiserum against holocytochrome c oxidase revealed that label was incorporated into three polypeptides of sizes equivalent to those of cytochrome c oxidase subunits I, II, and III, shown from earlier studies in vivo to be translated on mitochondrial ribosomes. Further evidence that these polypeptides made in vitro are "native" and identical to subunits I, II, and III was provided by the observation that labeled polypeptides equivalent in size to subunits I-III- ARE ALSO IMMUNO-PRECIPITATED BY ANTISERUM AGAINST SUBUNITS V plus VII, an antiserum that can precipitate subunits I, II, and III only when they are complexed to the cytoplasmically synthesized subunits, V and VII, of the enzyme. These results suggest that isolated mitochondria are capable of synthesizing three subunits of cytochrome c oxidase and assembling them into a holoenzyme.